2022
DOI: 10.24875/rccar.m21000049
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis infecciosa asociada al cuidado de la salud. Estudio de prevalencia en un hospital de alta complejidad

Abstract: Introducción: Los procedimientos vasculares invasivos ocasionan infecciones sanguíneas asociadas a cuidados de la salud, entre ellas endocarditis infecciosa. Este evento adverso conlleva mayor morbimortalidad que la endocarditis infecciosa adquirida en la comunidad. Objetivo: Evaluar la prevalencia de endocarditis infecciosa asociada al cuidado de la salud y describir las características demográficas de esta población, así como los agentes etiológicos. Método: Estudio de corte transversal, en el que se incluyó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…Like CoNS, MRSA is strongly associated with biofilm formation on intravascular devices, making infections persistent and difficult to treat [ 29 , 31 , 32 ]. Negative blood cultures occurred in about a third of the samples collected from the CIE group, a percentage similar to other Latin American studies [ 33 , 34 ]. This result can be explained by economic limitations resulting in restrictive access to serological tests and molecular biology techniques for diagnosing infections by fastidious bacteria and by using antimicrobials before collecting cultures.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Like CoNS, MRSA is strongly associated with biofilm formation on intravascular devices, making infections persistent and difficult to treat [ 29 , 31 , 32 ]. Negative blood cultures occurred in about a third of the samples collected from the CIE group, a percentage similar to other Latin American studies [ 33 , 34 ]. This result can be explained by economic limitations resulting in restrictive access to serological tests and molecular biology techniques for diagnosing infections by fastidious bacteria and by using antimicrobials before collecting cultures.…”
Section: Discussionsupporting
confidence: 86%
“…Other national studies reported similar rates [ 16 , 17 , 37 ], placing Brazil as one of the countries with the highest risk of death from IE [ 4 , 38 ]. Regarding cases of HAIE in this study and in other Latin American studies [ 16 , 23 , 33 , 34 ], the use of central intravascular catheters and BSI had a strong relationship with patients of nosocomial and non-nosocomial IE. Therefore, strengthening of infection prevention and control teams, healthcare professional training regarding insertion and care in central catheter management and staff awareness regarding compliance with care-related infection prevention measures are feasible actions to reduce HAIE rates [ 39 ].…”
Section: Discussionsupporting
confidence: 66%